3D interconnected hierarchical porous N-doped carbon constructed by flake-like nanostructure with Fe/Fe3C for efficient oxygen reduction reaction and supercapacitor. Issue 19 (4th May 2018) - Li, Guoning; Zhang, Jiajun; Li, Weisong; Fan, Kai; Xu, Chunjian
Abstract : 3D interconnected hierarchical porous Fe/N-doped carbon was facilely prepared via ZIF-8 as self-template and potassium ferricyanide as multifunctional iron precursor. Abstract : Hierarchical porous N-doped carbon with Fe/Fe3 C nanoparticles, high content of N dopants (10.51 wt%), and a 3D interconnected porous architecture constructed by flake-like nanostructure was facilely prepared by carbonization of a zeolitic imidazolate framework-8 (ZIF-8) as a self-sacrificing template and potassium ferricyanide (PF) as a multifunctional iron precursor. The unique porous structure can offer a continuous pathway for electron transfer and shorten the mass transfer pathway, which contribute to both an oxygen reduction reaction (ORR) and a supercapacitor. The influence of the carbonization temperature and iron content on the performance of ORR and supercapacitor was investigated. The as-prepared composites carbonized at 800 °C (Fe-CZIF-800-10) displayed comparable ORR activity with Pt/C in alkaline media as well as excellent long-term stability, superb methanol tolerance, and appreciable onset potential in acid media. Moreover, Fe-CZIF-800-10 exhibited excellent capacity of 246 F g −1 at a current density of 0.5 A g −1 and stability in 6 M KOH. This report provides a facile approach to prepare hierarchical porous Fe/N-doped carbon as a promising electrode material for both fuel cell and supercapacitor applications.